Legislative Voting Behaviour in the Regional Party System: An Analysis of Roll-Call Votes in the South Korean National Assembly, 2000–8. Issue 3 (23rd November 2015) - Shin, Jae Hyeok; Lee, Hojun
Abstract : This article explores legislative voting behaviour in the regional party system where electoral competition is based primarily on geographic divisions instead of national public policies. An analysis of roll-call votes in the National Assembly of the Republic of Korea from 2000 to 2008 reveals that in the regionalized context, legislative voting unity is high because legislators are disciplined to receive endorsement from their regional champion party. Those legislators are far more disciplined when voting on pork legislation. Nonetheless, as the socioeconomic status of constituents rises and the constituents thus care more about policy than pork, then opposition legislators tend to vote against their parties more often. Conversely, governing-party members are more disciplined to pass bills where voters often desire policy over pork. This study suggests a powerful interaction between party affiliations and voter demands as a dominant electoral strategic tool in the regional party system.